Surfing, scrolling and stressing: Technostress in browsing digital content feeds on smartphones from the gratifications and dimensions of use perspective - Hämäläinen, Antti; Salo, Markus; Pirkkalainen, Henri (Human Technology, 2024)
In this study, we investigate how the nature of activities users perform to interact with information delivered via smartphones (i.e., dimensions of smartphone use), along with gratifications sought and obtained, contribute to technostress in the context of digital content feeds. By applying qualitative research methods and analyzing data gathered through 30 semi-structured interviews, we identify five dimensions of smartphone use: instant, repeated, continuous, personalized, and versatile. Introducing the concept of smartphone use loop, we reveal the dynamic relationships between these dimensions, gratifications, and technostress, illustrating how different dimensions of use and underlying gratifications can lead to diverse technostress experiences (e.g., depending on whether the gratifications sought are obtained). Furthermore, we identify previously unexplored technostressors and strains, such as gratification mismatch and worsened boredom tolerance. By integrating uses and gratifications theory with technostress research, this study offers a novel framework for understanding the dual nature of smartphone use.